Metrology and theory of measurement - Slaev, Valery A.; Chunovkina, Anna G.; Mironovsky, Leonid A. (De Gruyter, 2020)
Metrology is the science of measurements. As such, it deals with the problem of obtaining knowledge of physical reality through its quantifiable properties. The problems of measurement and of measurement accuracy are central to all natural and technical sciences. Now in its second edition, this monograph conveys the fundamental theory of measurement and provides some algorithms for result testing and validation.- Resumé vydavatel
Keywords: meteorologie; měření; meteorology; measurement; elektronické knihy; monografie; electronic books; monographs